Keto Diet: Where Do We Stand Today? - M, Saifuddin (Bangladesh Journal of Medicine, 2024)
Ketogenic diet seems like the latest weight-loss craze, but it’s been around for nearly a century. Developed in 1920s, this ultra-low-carb, high-fat diet was originally used to treat seizures in people with epilepsy but grab attention and popular among young generation and Diabetic patients for rapid weight reduction and hope to get numerous health benefits against Diabetes, Cancer, certain neurological disorders including Alzheimer's disease. Diabetic patients are following the diet as some people claim that reversal to non-Diabetic state and controlling Diabetes without any medication is also possible with this diet. Ketogenic diet involves drastically reducing carbohydrate intake and replacing it with fat aiming to force the body into metabolizing fat instead of carbohydrates. Burning fat seems like an ideal way to lose weight and reduce appetite. The classic Ketogenic diet is not a balanced diet and has numerous risks. Ketogenic diet is high in saturated fat with link to atherosclerosis and heart disease. There is risk of Diabetic ketoacidosis due to discontinuation of Anti Diabetic medication or patients on SGLT2 inhibitor. Other potential risks include nutrient deficiency, deterioration of existing liver disease, renal problems due to protein overload and increased risk of osteoporosis. Available research on the Ketogenic diet for weight loss is still limited with a small number of participants for a limited period and without control groups. So long term outcome of Ketogenic diet is uncertain as very low carb diet is difficult to sustain with numerous risk and possibility of weight gain after giving up of Ketogenic diet. Bangladesh J Medicine, 2024; Vol. 35, No. 2, Supplementation: 148-149